Efficacy of Laparoscopic Surgery Combined With Leuprorelin in the Treatment of Endometriosis Associated With Infertility and Analysis of Influencing Factors for Recurrence - Yu, Lu; Sun, Yunming; Fang, Qiongyan (Frontiers in Surgery, 2022)
Objective To explore the curative effect of laparoscopic surgery combined with leuprorelin in the treatment of endometriosis with infertility and the related factors of recurrence after treatment. Methods A total of 158 patients with endometriosis and infertility were selected in our hospital from January 2019 to June 2020. They were divided into the control group and the observation group with 79 patients in each group by random number table method. The control group was treated by laparoscopy surgery combined with dydrogesterone, and the observation group was treated with laparoscopic surgery combined with leuprorelin. The hormone levels, recurrence rate, pregnancy rate and adverse reaction were compared between the two groups. The related factors of postoperative recurrence were analyzed based on the clinical and pathological information. Results After treatment, the levels of luteinizing hormone, follicle-stimulating hormone and estradiol in the observation group were lower than those in the control group (P<0.05). The recurrence rate at 12 months after operation in the observation group was lower than that in the control group (P<0.05). The pregnancy rates in the observation group were higher than those in the control group (P<0.05). There was no significant difference in the incidence of adverse reactions between the two groups (P>0.05). Univariate analysis showed that preoperative dysmenorrhea, postoperative medication and postoperative pregnancy had an impact on the postoperative recurrence of endometriosis (P<0.05). Multivariate analysis showed that preoperative dysmenorrhea was an independent risk factor for postoperative recurrence in patients with endometriosis (P<0.05). Postoperative pregnancy was a protective factor for postoperative recurrence in patients with endometriosis (P<0.05). Conclusion Laparoscopy combined with leuprorelin in the treatment of endometriosis associated with infertility can improve hormone levels and pregnancy rate, and the recurrence rate is low. Preoperative dysmenorrhea is an independent risk factor for postoperative recurrence, which should be quantified and included in the recurrence risk prediction model. Postoperative pregnancy can reduce the recurrence rate after surgery, and patients with fertility requirements should be encouraged to actively prepare for pregnancy after surgery.